Accuracy of Clinical Diagnosis of Dengue Episodes in the RV144 HIV Vaccine Efficacy Trial in Thailand. - Punnee Pitisuttithum; Supachai Rerks-Ngarm; Donald Stablein; Peter Dawson; Sorachai Nitayaphan; Jaranit Kaewkungwal; Nelson L Michael; Jerome H Kim; Merlin L Robb; Robert J O'Connell; In-Kyu Yoon; Stefan Fernandez; et al. (PLoS ONE, 2015)
RV144 was a community-based HIV vaccine efficacy trial conducted in HIV-uninfected adults in Thailand, where dengue virus continues to cause a large number of infections every year. We attempted to document the accuracy of clinically diagnosed dengue episodes reported as serious adverse events (SAEs) and adverse events (AEs) and examine whether dengue serology would support the clinical diagnosis. Subjects without a clinical dengue diagnosis but with an infection or idiopathic fever were selected as a control population. Dengue serology was performed by hemagglutination inhibition on plasma samples. A total of 124 clinical dengue episodes were reported (103 SAEs and 21 AEs). Overall 82.6% of the clinically diagnosed dengue episodes were supported by a positive dengue serology: 71.4% of the AEs and 85.0% of the SAEs. Of the 100 subjects with both clinical dengue and positive serology, all presented with fever, 83% with leucopenia, 54% with thrombocytopenia, and 27% with hemorrhagic symptoms. All episodes resolved spontaneously without sequellae. Only two of 15 subjects with a negative serology presented with fever. The sensitivity and specificity of clinical dengue diagnosis were 90.9% and 74.4%, respectively, when compared to the control population, and with a positive predictive value of 82.6% and negative predictive value of 84.7% when compared to dengue serology. Clinical diagnosis of dengue is an accurate method of dengue diagnosis in adults in Thailand. Large-scale clinical trials offer the opportunity to systematically study infectious diseases such as dengue and other infections that may occur during the trial.